Effect of Preharvest 1-MCP Treatment on the Flesh Firmness of ‘Rojo Brillante’ Persimmon - Vilhena, Nariane Q.; Gil, Rebeca; Vendrell, Mario; Salvador, Alejandra (MDPI, 2022)
This study investigated the effect of preharvest 1-MCP treatment on maintaining ‘Rojo Brillante’ persimmon firmness. Early in the season, preharvest 1-MCP was applied 1, 7 and 10 days after ethephon treatment. The fruit firmness was evaluated during three different harvests and after the commercialization period of 3 d at 3 °C, plus 6 d at 20 °C. Late in the season, 1-MCP was applied 3 days before harvest in the fruit treated with gibberellic acid (GA) and then cold-stored for up to 60 days, plus a 6-day shelf life at 20 °C. The results showed that preharvest 1-MCP delayed the fruit softening induced by ethephon during the harvest period, and was the most effective treatment when performed 1 day after ethephon application. Therefore, preharvest 1-MCP extended the harvest period of ethephon-treated fruit. At the end of the season, preharvest 1-MCP had the same effect on maintaining the fruit firmness as the commercial postharvest application.